Chia seed-mediated fabrication of ZnO/Ag/Ag2O nanocomposites: structural, antioxidant, anticancer, and wound healing studies - Rafique, Aisha; Amjad, Fatima; Janjua, Muhammad Ramzan Saeed Ashraf; Naqvi, Syed Ali Raza; Hassan, Sadaf Ul; Abdullah, Hanzla; Nazir, Muhammad Shahid; Ali, Zulfiqar; Alshihri, Abdulaziz A.; Momenah, Maha Abdullah; Mansour, Adel Abo; Bajaber, Majed A.; et al. (Frontiers in Chemistry, 2024)
Plant extract mediated fabrication of metal nanocomposites, employed in cell proliferation inhibition and topical wound treatment, demonstrating the significant effectiveness. Salvia hispanica L. (chia) seed extract (CE) used as the reaction media for the green fabrication of ecofriendly ZnO(CE) nanoparticles (NPs), Ag/Ag2O(CE), and ZnO/Ag/Ag2O(CE) nanocomposite. The resultant nanoparticles and nanocomposite materials were characterized using UV-visible, FTIR, SEM, XRD and EDX techniques. In context of antioxidant studies, ZnO/Ag/Ag2O(CE) exhibited 57% reducing power and 86% DPPH (2,2, diphenyl-1-picrylhydrazyl) free radical scavenging. All the three materials showed strong anti-bacterial activity against Staphalococus aureus (S. aureus), Escherichia coli (E.coli) and Bacillus subtilis (B. subtilis) bacterial strains. Additionally, ZnO(CE), Ag/Ag2O(CE), and ZnO/Ag/Ag2O(CE) also revealed 64.47%, 42.56%, and 75.27% in-vitro MCF7 (Michigan Cancer Foundation-7) cancer cell line inhibition, respectively at 100µg/mL concentration. Selectively, the most effective composite material, ZnO/Ag/Ag2O(CE), were used, to evaluate in-vivo wound healing potential, in rat models. The study revealed 96% wound closure in 10 days, that was quite rapid healing as compare to wound healing using clinically available ointment. Therefore, in conclusion, ZnO/Ag/Ag2O(CE) nanocomposite material could be considered for further testing and formulation as a good anticancer and wound healing agents.